Exploring the Impacts of the Covid-19 Pandemic on English Language Teachers - Sukirman Sukirman (Universitas Islam Negeri Walisongo Semarang, 2023)
This study aims to assess how Indonesian Islamic higher education, specifically English language teachers, have been impacted by the Covid-19 pandemic. The researcher conducted semi-structured interviews to investigate the impacts of Covid-19 on English language teachers. Data were collected from ten participants, and thematic analysis techniques were used to analyze the data, including data familiarization, generating codes, grouping codes, generating themes, and finalizing findings. The study reveals that the pandemic has significantly impacted education, particularly English language teaching. It has led to a loss of interactive classroom experiences and obstacles to language acquisition. However, participants have benefited from increased accessibility to international seminars, workshops, and conferences. It has removed geographical and financial barriers, allowing participants to attend events at no cost and providing valuable educational advantages. Future research could benefit from larger-scale participation. In that case, a better understanding of the impact of valuable educational advantages gained from international events amidst Covid-19 on teachers’ teaching performances in the post-pandemic needs to be developed.